Bus rapid transit in Solo, Indonesia: Lessons from a low ridership system. Issue 2 (June 2020) - Guerra, Erick; Gamble, Julie; Taylor, John
Highlights: Examines a system at the bottom of global rankings of BRT ridership. Discusses the history and challenges of BRT implementation in Solo, Indonesia. Presents results of on-board survey of informal transit users. Finds that the new bus system is not a suitable replacement for informal transit. Concludes with challenges of BRT in cities with high motorcycle use.